2022
DOI: 10.4018/ijabim.294102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media Marketing on Overall Brand Equity in the Telecommunication Sector in Bangladesh

Abstract: The objective of this study is to investigate the role of social media marketing (SMM) on overall brand equity (OBE) via value co-creation (VC) in the telecommunication sector in Bangladesh. Moreover, brand love is tested as a moderator of SMM and VC. A structured questionnaire was distributed to collect survey data from 241 mobile subscribers using a systematic sampling method from different areas of Dhaka city in Bangladesh. The hypotheses were examined using structural equation modeling (SEM). The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Secondly, this study has considered a recent growing economy: Bangladesh, to draw the study sample as it is observed that the country has been experiencing a digital transformation across the nation [ 20 ], where eWOM plays a critical role in developing the business growth, especially on online platforms. Lastly, several studies in Bangladesh were carried out to exhibit the connection of social media with brand equity [ 21 ], consumer behavior [ 22 ], and purchase intention [ 23 , 24 ]. In contrast, the relationship between various attributes of eWOM and consumer behavioral aspects was rarely tested in the Bangladesh context, where social media-based businesses have started flourishing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this study has considered a recent growing economy: Bangladesh, to draw the study sample as it is observed that the country has been experiencing a digital transformation across the nation [ 20 ], where eWOM plays a critical role in developing the business growth, especially on online platforms. Lastly, several studies in Bangladesh were carried out to exhibit the connection of social media with brand equity [ 21 ], consumer behavior [ 22 ], and purchase intention [ 23 , 24 ]. In contrast, the relationship between various attributes of eWOM and consumer behavioral aspects was rarely tested in the Bangladesh context, where social media-based businesses have started flourishing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…E-WOM is one dimension encompassed by social media marketing (SMM). SMM has a significantly positive effect on overall brand equity (Hafez, 2021). Twitter is a good platform for e-WOM, especially favorites (likes) and retweets (shares) that can help spread messages and enhance interaction among customers (Alboqami et al, 2015;Chu & Sung, 2015;Kim et al, 2014;Mucan & Özeltürkay, 2014;Weerawatnod et al, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%